Inovasi Layanan Publik dalam Era Digital: Tinjauan Persepsi Generasi Muda pada Samsat Digital di Lumajang - Afandi Afandi; Zainal fatah; Sri Roekminiati; Ika Devy Pramudiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores the digital transformation of public services through SAMSAT Digital in Lumajang, Indonesia, focusing on the perceptions of the younger generation. The implementation of SAMSAT Digital aims to improve accessibility, efficiency, transparency, and user experience in vehicle administrative services. The research highlights that the success of this digital innovation depends on key factors such as ease of use, data security, and service speed. The integration of advanced features like intuitive interfaces, proactive notifications, AI-powered chatbots, and flexible digital payments significantly enhance user satisfaction and adoption, especially among tech-savvy youths. Challenges such as limited digital literacy and infrastructural issues require continuous education and infrastructure improvements. Overall, the findings demonstrate that effective digital service innovation, supported by a strong commitment to security, usability, and infrastructural development, can foster more effective, transparent, and inclusive public services, contributing to better quality of life and modern governance.